2022
DOI: 10.3389/fenvs.2022.950482
|View full text |Cite
|
Sign up to set email alerts
|

Urea hydrolysis in different farmland soils as affected by long-term biochar application

Abstract: Urea is a commonly used nitrogen (N) fertilizer that contributes to world food production, and there have been increasing concerns about relatively low urea-N use efficiency. Biochar has shown the potential to mitigate N loss, but how biochar influences urea hydrolysis and the underlying mechanisms are still unclear. In this study, long-term biochar-amended upland, paddy and greenhouse soils were sampled at depths of 0–20 and 20–40 cm in Haicheng City, Northeast China. Soil N contents, urea hydrolysis rates (U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 60 publications
1
5
0
Order By: Relevance
“…The increased URE activity observed in the amended soils, together with the reduction of total N content (Table 1), was likely indicative of a stimulation of urea hydrolysis due to biochar rather than an increased microbial content in amended soils (i.e., SMB reduced in 2.5-and 5.0-Bio; Figure 3). Such accelerated rate of URE activity in the presence of biochar was recently reported by Zhao et al [75] and could be partly responsible for the N reduction observed in the amended soils (especially 5.0-Bio; Table 1). The increased URE observed in the amended soils can also be due to an increased microbial synthesis of the enzyme stimulated by a more limited N availability in these soils [76], which in turn can be explained by NO 3 -N and NH 4 -N adsorption by biochar, as previously observed [19].…”
Section: Influence Of Biochar On Soil Enzyme Activities and Community...supporting
confidence: 70%
“…The increased URE activity observed in the amended soils, together with the reduction of total N content (Table 1), was likely indicative of a stimulation of urea hydrolysis due to biochar rather than an increased microbial content in amended soils (i.e., SMB reduced in 2.5-and 5.0-Bio; Figure 3). Such accelerated rate of URE activity in the presence of biochar was recently reported by Zhao et al [75] and could be partly responsible for the N reduction observed in the amended soils (especially 5.0-Bio; Table 1). The increased URE observed in the amended soils can also be due to an increased microbial synthesis of the enzyme stimulated by a more limited N availability in these soils [76], which in turn can be explained by NO 3 -N and NH 4 -N adsorption by biochar, as previously observed [19].…”
Section: Influence Of Biochar On Soil Enzyme Activities and Community...supporting
confidence: 70%
“…First, because NH 3 volatilisation is considered the major pathway of N loss in agricultural systems resulting from N fertilizer application (Sha et al, 2019; Sun et al, 2017). More directly, our previous study conducted on the same maize biochar and soil showed that by accelerating urea hydrolysis rates and increasing soil pH (Liu et al, 2021), biochar could change the equilibrium dynamics of NH4+$$ {{\mathrm{NH}}_4}^{+} $$‐N dissociation, thereby stimulating NH 3 volatilisation and resulting in a lower NH4+$$ {{\mathrm{NH}}_4}^{+} $$‐N content in the soil (Liu et al, 2017; Zhao et al, 2022). This scenario was also illustrated by former researchers (Esfandbod et al, 2017; Yao et al, 2022) that by promoting NH 3 volatilisation, biochar reduced the availability of NH4+$$ {{\mathrm{NH}}_4}^{+} $$‐N, thereby delaying soil nitrification.…”
Section: Discussionmentioning
confidence: 99%
“…Ureolysis was also significantly increased in the OM rhizosphere. Manure amendments are known to provide urea to the soil, that can constitute a source of nitrogen for plants due to the presence of ureolytic microorganisms [92] , [93] . Overall, our results suggest that sheep manure favor the presence of bacteria involved in beneficial processes such as improved nutrient cycling, degradation of recalcitrant pollutants and defense against soil borne pathogens.…”
Section: Discussionmentioning
confidence: 99%